Affective Variables of Second Language Acquisition: Language Learning Anxiety - Dadaboev, Dilshodjon; Anis, Houssam (The Lingua Spectrum, 2025)
One area of focus in the TESOL field is language learning anxiety. One way to describe anxiety is as a personal emotion of shyness, inhibition, or inferiority. Anxiety related to language acquisition has revealed several aspects that can be both beneficial and detrimental. These can be evident in the ways that language skills, ambiguity tolerance, and the influence of foreign experience manifest. It is true that previous research areas have investigated language competency in great detail. Nonetheless, the topics of foreign experience and ambiguity tolerance may be regarded as novel research topics. Additionally, studies examining the connection between bilingualism, language competency, including language certificates, and the level of communicative anxiety in language X (in this example, English), a third language. Furthermore, it is crucial to investigate the connection between the level of communicative anxiety in the language X (in this case, English), language proficiency, including language certificates, and bilingualism. The current work’s arguments are important in a few ways. First, because they lack the "document," which is proof of language proficiency, speakers may feel excluded or constrained with a sense of inequality. Then, regardless of great language skill, the issue that significantly affects EFL learners is tolerance of ambiguity in native context.